Reframing responsibility in an era of responsibilisation: education, feminist ethics. Issue 1 (2nd January 2017) - McLeod, Julie
ABSTRACT: Late modern social theories and critiques of neoliberalism have emphasised the regulatory and negative aspects of responsibility, readily associating it with self-responsibility or analytically converting it to the notion of responsibilisation. This article argues for stepping back from these critiques in order to reframe responsibility as a relational disposition and practice in education that warrants a fresh look. Feminist scholarship on the ethics of care, affective equality and relational responsibility are revisited in light of a consideration of teachers' work and educational purposes. It is argued, first, that there is an urgency for repositioning responsibility as a productive orientation and practice, given definitions of teaching are increasingly instrumental. Second, feminist theories of care and relational responsibility remain relevant to normative discussions of education and its knowledge and person-making purposes. Third, critical engagements with the affective and social circumstances of precarity bring new challenges for how educational institutions might respond to a pervasive sense of vulnerability, and accompanying opportunities and demands for care, interdependence and relational responsibility – towards others, not only the self.